2014
DOI: 10.1111/nph.12908
|View full text |Cite
|
Sign up to set email alerts
|

The context dependence of beneficiary feedback effects on benefactors in plant facilitation

Abstract: Summary Facilitative effects of some species on others are a major driver of biodiversity. These positive effects of a benefactor on its beneficiary can result in negative feedback effects of the beneficiary on the benefactor and reduced fitness of the benefactor. However, in contrast to the wealth of studies on facilitative effects in different environments, we know little about whether the feedback effects show predictable patterns of context dependence. We reanalyzed a global data set on alpine cushion pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 75 publications
(112 reference statements)
6
73
0
Order By: Relevance
“…A recent global study in alpine regions evidenced that increasing cover of beneficiary species limited the reproductive output of associated nurse plants (Schöb et al, 2014b), suggesting that a possible increase in the growth rate of alpine beneficiary species because of warming (e.g., Pajunen et al, 2011) may have a negative impact on nurse plants, eventually being a possible cause of population extinction. However, another study observed a reduced negative effect of beneficiary species on nurse plants in more productive ecosystems (Schöb et al, 2014a), possibly indicating that in warmer, more productive environments, negative feedback effects of beneficiary species on nurse plants might diminish. From these seemingly contradictory viewpoints, understanding the feedback effects of beneficiary species on nurse plants in the face of climate change constitutes an important and challenging topic for the future.…”
Section: Facilitation In Established Alpine Communities: a Bibliograpmentioning
confidence: 99%
“…A recent global study in alpine regions evidenced that increasing cover of beneficiary species limited the reproductive output of associated nurse plants (Schöb et al, 2014b), suggesting that a possible increase in the growth rate of alpine beneficiary species because of warming (e.g., Pajunen et al, 2011) may have a negative impact on nurse plants, eventually being a possible cause of population extinction. However, another study observed a reduced negative effect of beneficiary species on nurse plants in more productive ecosystems (Schöb et al, 2014a), possibly indicating that in warmer, more productive environments, negative feedback effects of beneficiary species on nurse plants might diminish. From these seemingly contradictory viewpoints, understanding the feedback effects of beneficiary species on nurse plants in the face of climate change constitutes an important and challenging topic for the future.…”
Section: Facilitation In Established Alpine Communities: a Bibliograpmentioning
confidence: 99%
“…Regular patterns are thought to be the consequence of competition operating at certain intermediate scales when compared with facilitation (Peter andElke 2005, von Hardenberg et al 2010). This result suggests that, in shrublands, the number of facilitated species is constraining the ability of nurses to increase patch sizes, probably because the more individuals are present in an area, the less they can grow (Schöb et al 2014). It is worth noting that separating direct facilitation effects from other co-occurrence mechanisms such as seed trapping or habitat sharing is challenging from observational data (Cipriotti andAguiar 2015, Delalandre andMontesinos-Navarro 2018).…”
Section: Factors Related To the Shape Of Patch-size Distributions Arementioning
confidence: 99%
“…A second case from a very different study system is the importance of context for beneficial interactions on facilitation effects in alpine cushion plants. Schöb et al . (pp.…”
Section: Surprising Interactions and Outcomesmentioning
confidence: 99%